Arabidopsis Trichome Contains Two Plasma Membrane Domains with Different Lipid Compositions Which Attract Distinct EXO70 Subunits - Kubátová, Zdeňka; Pejchar, Přemysl; Potocký, Martin; Sekereš, Juraj; Žárský, Viktor; Kulich, Ivan (International journal of molecular sciences, 2019)
Plasma membrane (PM) lipid composition and domain organization are modulated by polarized exocytosis. Conversely, targeting of secretory vesicles at specific domains in the PM is carried out by exocyst complexes, which contain EXO70 subunits that play a significant role in the final recognition of the target membrane. As we have shown previously, a mature Arabidopsis trichome contains a basal domain with a thin cell wall and an apical domain with a thick secondary cell wall, which is developed in an EXO70H4-dependent manner. These domains are separated by a cell wall structure named the Ortmannian ring. Using phospholipid markers, we demonstrate that there are two distinct PM domains corresponding to these cell wall domains. The apical domain is enriched in phosphatidic acid (PA) and phosphatidylserine, with an undetectable amount of phosphatidylinositol 4,5-bisphosphate (PIP2), whereas the basal domain is PIP2-rich. While the apical domain recruits EXO70H4, the basal domain recruits EXO70A1, which corresponds to the lipid-binding capacities of these two paralogs. Loss of EXO70H4 results in a loss of the Ortmannian ring border and decreased apical PA accumulation, which causes the PA and PIP2 domains to merge together. Using transmission electron microscopy, we describe these accumulations as a unique anatomical feature of the apical cell wall-radially distributed rod-shaped membranous pockets, where both EXO70H4 and lipid markers are immobilized.
Keywords: Phosphatidylserines; proteiny huseníčku; vezikulární transportní proteiny; Exocytosis; Arabidopsis; Vesicular Transport Proteins; Phosphatidylinositol 4,5-Diphosphate; trichomy; buněčná membrána; Arabidopsis Proteins; Membrane Lipids; fosfatidylseriny; Trichomes; exocytóza; fosfatidylinositol-4,5-difosfát; Cell Membrane; membránové lipidy